A teacher of teachers. Pedro de Alcántara García Navarro (1842-1906) and the Protective Society of the Children of Madrid (Foro de Educacion, 2024)
In the last quarter of century XIX, the cordovan Pedro de Alcántara García Navarro emphasized in multiple pedagogical facets. Its bibliographical work was exceptional and excellent the works that carried out for the introduction, in our country, of the educative innovations that were being tried outside our borders. In addition, his participation in multiple pedagogical congresses was very important.In union to Julio Vizcarrondo and Cristóbal Colón de la Cerda , he collaborated to found, in 1878, the deprived beneficial institution: Protective Society of the Children of Madrid.Years later (1893), the organization established the Hospital-Refuge and the schools, where it took shelter and education to the orphaned and left children was dis- tributed. In these last ones, the welcome and education were offered in declared hygienic conditions like model. The used training material was of most novel and the application of an innovating methodology broke with the traditional repetition and memory.